1993
DOI: 10.1080/09553009314552161
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Vitamins C and E Against γ-ray-induced Chromosomal Damage in Mouse

Abstract: The effects of vitamins C and E on bone marrow chromosomes of the mouse exposed to 1 Gy of whole-body gamma-irradiation were studied. These vitamins, dissolved in water/peanut oil, were administered orally as acute doses, either 2 h before, immediately after, or 2 h after irradiation. Both vitamins significantly reduced the frequencies of micronuclei and chromosomal aberrations in bone marrow cells; radioprotection by vitamin E was, however, appreciably greater than that afforded by vitamin C. Administration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(59 citation statements)
references
References 20 publications
3
51
0
1
Order By: Relevance
“…It was reported previously that in vitro protection against radiation-induced micronucleus formation in human lymphocytes by vitamin C, vitamin E or β-carotene was more effective when antioxidants were added after the radiation exposure than before (17). An in vivo study showed that vitamin C or vitamin E was equally as effective in reducing γ-radiation-induced bone marrow micronucleus formation and chromosomal aberrations when given to mice 2 h before or after irradiation (44). These two studies evaluated the protective effects of antioxidant vitamins only at radiation doses of 1 and 2 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported previously that in vitro protection against radiation-induced micronucleus formation in human lymphocytes by vitamin C, vitamin E or β-carotene was more effective when antioxidants were added after the radiation exposure than before (17). An in vivo study showed that vitamin C or vitamin E was equally as effective in reducing γ-radiation-induced bone marrow micronucleus formation and chromosomal aberrations when given to mice 2 h before or after irradiation (44). These two studies evaluated the protective effects of antioxidant vitamins only at radiation doses of 1 and 2 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that vitamin E reduces radiation injury through its antioxidant effects (Sarma and Kesaven, 1993). Erol et al (2004) examined MDA levels and histopathological features in rats' brains subjected to gamma irradiation, and found that treatment after irradiation with vitamin E prevented neural tissue necrosis in radiation-damaged brain tissue.…”
Section: Vitamin Ementioning
confidence: 99%
“…16 Vitamin E therapy decreases the radiation injury by its antioxidant effects by preventing free radicals. 17 Walden et al 18 demonstrated the protective effects of Prostaglandin E2 in whole body irradiated rats. CAPE is an active component of propolis, which is a popular folk medicine in various countries possessing a broad spectrum of biological activities, including anticancer, antioxidant, antiinflammatory, antibiotic, antifungal and antihepatotoxic effects.…”
Section: Discussionmentioning
confidence: 99%